Pengaruh Daya Tarik Iklan dan Citra Merek Bb Cushion Pixy terhadap Keputusan Pembelian: Survei pada Mahasiswi Manajemen Universitas Perjuangan Tasikmalaya - Jessica Graciana (CV. Ulil Albab Corp, 2022)
The purpose of this study was to determine the effect of the attractiveness of BB Cushion Pixy's advertisements on decisions, the effect of BB Cushion Pixy's brand image on purchasing decisions (Survey of Management students at Universitas Perjuangan Tasikmalaya). The research method used is the causal method. The data used are primary data and secondary data. The data analysis technique used in this research is multiple regression analysis. Based on the results of the study, it is known that the attractiveness of advertising and brand image simultaneously significantly influence the purchasing decision of BB Cushion Pixy. The attractiveness of advertising has a significant partial effect on purchasing decisions for BB Cushion Pixy. Brand image partially significant effect on purchasing decisions BB Cushion Pixy.